EVALUASI PENGGUNAAN ANTIBIOTIKA PADA PASIEN PEDIATRI PENDERITA DIARE DI INSTALASI RAWAT INAP RSUD KOTA MADIUN PERIODE NOVEMBER – DESEMBER 2015 - Kartikaningrum, Vidya (Widya Warta, 2017)
Diarrhea is a disease marked by the increasing frequency of defecation more than three times a day accompanied by liquid stools with or without blood or mucus. According to Word Gastroenterology Organization (2012), children with acute diarrhea can be healed by oral rehydration theraphy, zink supplement theraphy, diet, probiotics, and antibiotics. The purpose of this research was to evaluate the rational prescription of antibiotics for child patients suffering from diarrea in Madiun City Hospital. The research subjects were sixty nine patients; the method of collecting data was purposive sampling. The data of this non experimental research were retrospectively obtained from medical record and descriptively analyzed. The research result showed that in Madiun City Hospital antibiotic was given with right indication 59,02%, with the right patients 100%, with the right drug 100%, and the right dose 78,85%.